Latent Profiles of Responding on the Massachusetts Youth Screening Instrument-2 Subscale Scores by Race/Ethnicity among Juvenile Justice-Involved Boys and Girls - Jaggers, Jeremiah W. (Youth violence and juvenile justice, 2023)
The Massachusetts Youth Screening Instrument (MAYSI-2) is one of the most widely utilized screening measures for detecting mental health concerns among youth entering juvenile detention settings. Previous research has demonstrated clear patterns of sex differences in the severity of mental health symptoms among detained boys and girls. However, few studies have examined potential racial or ethnic differences in MAYSI-2 scores, which is a significant limitation. This study examined sex and racial/ethnic differences in patterns of youth responses on the MAYSI-2. Data were collected from a total of 5417 youth detained in a short-term detention facility in the Mountain West. Results of latent profile analyses demonstrated that, among both boys and girls, youths’ racial/ethnic identity was associated with distinct patterns of responding on the MAYSI-2. These findings have implications for informing screening in the juvenile justice system and increasing recognition and response to ethnic/racial and sex differences among detained youth.